Місцеве лікування підгострого тиреоїдиту - Бурдо, І. С.; Моторний, Є. О.; Комісаренко, І. В. (Clinical Endocrinology and Endocrine Surgery, 2013)
This article describes the case of local treatment of subacute thyroiditis by method of dexametasone solution injection in thyroid gland tissue.